AN OVERVIEW ON THE MISCONCEPTIONS OF 6th GRADE STUDENTS ON THE SUBJECT OF FORCE AND MOTION WITH THE CHANGE IN CURRICULUM - Mustafa YILMAZLAR (Fırat University, 2019)
Science and technology eduation plays an important role in the orientation of the future life of the people. In addition it is inevitable when considering the relationship of science and technology lesson and life.The aim of the this study is to determine whether there is a change at the concept error about the action and evaluation at 6th grade students after the change in the programme. In this study, a literature survey has been done to identify the concept error in action and evaluation. Concept error tests which are multiple choices and paralel to eachother has been prepared. The distractor which are existed of four choices are prepared including concept error. A minor survey has been done by applying this tests to 6th grade students in İzmit. The tests have been applied in 7 schools. The 1st test including concept errors are applied to 235, 2nd test to 231 and the total number is 466. By looking at the validity and reliability of these tests not-working questions are eliminated and concept error test is composed of 33 questions. This test has been applied to 6th grade students in 5 primary school in Sakarya. The total student number is 425. The data that are acquired has been analyzed by using t-test and One-way ANOVA. By looking the consequences of the results, it has been searched whether concept errors are continuing or not. At the finding parts of the survey, there is a comparasion of the workings about the before and after of the cirruculum vitae changings. Both the results of the after the survey and the ideas of science and technology teachers about the concept error of action and evaluation, it has been determined that there is not so many changes at the concept error.